The influence of institutional quality on environmental efficiency of energy consumption in BRICS countries - Rasheed, Noman; Khan, Dilawar; Magda, Róbert (Frontiers in Energy Research, 2022)
It has been observed in the literature that efficient energy use reduces production cost and carbon emissions into the environment. This study further argues that institutional quality enhances environmental efficiency of energy consumption. Therefore, this study was carried out with the aim of exploring the influence of institutional quality on environmental efficiency of energy use in BRICS countries for the period from 2001 to 2020. A two-step procedure was carried out to achieve the objectives of this study. First, the environmental efficiency of energy consumption was estimated using the stochastic Frontier analysis (SFA) technique. The results of the SFA approach show that the average environmental efficiency of energy use in BRICS countries is 61%, ranging from 37.5 to 100%. Furthermore, there is 39% room for improvement in environmental efficiency of energy use in BRICS countries. Moreover, the SFA results also indicate that South Africa has the highest average environmental efficiency, and China has the lowest environmental efficiency score among BRICS countries. Second, this study employed the system GMM technique to explore the impact of institutional quality on environmental efficiency of energy consumption in BRICS countries. The results of the system GMM show that institutional quality plays a significant role in improving environmental efficiency of energy consumption in BRICS countries. Finally, this study recommends some policy measures based on the study’s findings to improve environmental efficiency of energy consumption.